Prediction of Chicken Meat Availability in Cilegon City Using iThink Dynamic Simulation Model - Firdaus, Muhamad Haikal; Sauri, Ahmad Sopyan; Turrohman, Syaifa; Tosida, Eneng Tita; Subandi, Kotim; Sugara, Victor Ilyas (Operations Research: International Conference Series, 2025)
The availability of chicken meat is a crucial factor in maintaining price stability and food security in Cilegon City. The increasing demand, influenced by population growth and consumption patterns, must be balanced with optimal supply from farmers and distributors. This study aims to predict the availability of chicken meat using a dynamic simulation model based on iThink. This model is built with a stocks and flows approach and causal loop diagrams to understand the dynamics of the system involving production, import, distribution, consumption, and external factors such as government policies and weather conditions. The simulation results show that the balance of supply and demand is greatly influenced by the level of local production, per capita consumption levels, and import policies. The simulation scenario also reveals that increasing production efficiency and optimizing distribution can increase the availability of chicken meat in the market by 15-20% in the next five years. This model is expected to be a tool for stakeholders in formulating more adaptive policies to maintain the stability of supply and prices of chicken meat in Cilegon City.